An Examination of Challenges Militating against Development of Guidance and Counseling in Nigerian Schools (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper examined the challenges facing teaching and learning of Guidance and Counseling programme in the Nigerian schools. The paper concluded that limited funding, shortage of trained counsellors, lack of proper infrastructure, societal and cultural problems, shortage of counseling resources, insecurity problems and poor capacity development of counsellor are challenges facing teaching and learning of Guidance and Counseling programme in the Nigerian schools. Based on this findings, the paper recommends increment in the funding guidance and counseling programme in the Nigerian schools by the government and stakeholders. Employment of more professional guidance and counseling teachers in all the schools in Nigeria by the governments to improve the service delivering of the guidance and counseling in schools across Nigeria. Provision of infrastructure facilities in all the schools by the government to support effective implementation of guidance and counselling programme. The government should provide adequate guidance and counseling resources in the schools. This will help to improve the quality of guidance and counseling services in the public schools across the country.